Holograficzny model reminiscencji w poezji Czesława Miłosza - Rydz, Agnieszka (Wydawnictwo Naukowe UAM, 2011)
For a model of nostalgic memory in the poetry of Czesław Miłosz, based on the psychological phenomenon of reminiscence, an allegoric counterpart can be identified in the hologram metaphor (Douwe Draaisma). The question: “Who am I” – reappears in Miłosz’s late lyrical poetry when he ponders over both his biography and the biographies of others. The response is provided, for instance, in the concept of human dialectic biography (of subject and object), formulated by Paul Ricoeur in his philosophical analyses. Human memory remains equally dialectic, placed in the antinomy between memory and oblivion. Still, retrieving a detail which has been remembered evokes all experience along with its rich context. That is the holographic effect, described in literature as the “ghost image”. Also in poetry, the effacing of memory trace does not make a barrier for the restitution of recollection. “The Sun of Memory” beams through the lyric of the author of the collection of poems “This”.
A holographic model of reminiscence in the poetry of Czesław Miłosz